The Effect of Health Education with PHBS Media on the Knowledge Level of Santri Pondok Zam-Zam Islamic Boarding School, Cilongok - Maulidian, Krisna; Linggardini, Kris (Proceedings Series on Health & Medical Sciences, 2022)
Clean and healthy living behavior (PHBS) is one way to maintain health to avoid various diseases caused by bacteria and viruses. The boarding school environment that applies dormitory education makes the spread of diseases often occur such as scabies (skin disease), scabies, diarrhea, ARI. Knowledge of PHBS coupled with behavior is very important to avoid the disease. The dissemination of knowledge using video is more attractive to students so that the enthusiasm to learn about the importance of PHBS will be conveyed.To determine the effect of health education with the video media on Clean and Healthy Behavior (PHBS) on the knowledge level of students at the Zam-Zam Islamic Boarding School Cilongok.This study uses quantitative research, with a pre-experimental design and a one- group pretest-posttest approach without control design. The sample used in this study were 60 respondents, the sampling technique was cluster sampling.The results showed that the knowledge score before intervention with an average of 18.76 with a standard deviation of 2.94 increased to 25.96 with a standard deviation of 0.86. The results of bivariate analysis using the Wilcoxon test, obtained a Z value of -6749 and a significance value of 0.0001 (p <0.05). There is an effect of health education with the media of Clean and Healthy Behavior (PHBS) video on the knowledge level of students at the Zam-Zam Islamic Boarding School Cilongok